PRC2 Represses Hormone-Induced Somatic Embryogenesis in Vegetative Tissue of Arabidopsis thaliana - Mozgová, Iva; Muñoz-Viana, Rafael; Hennig, Lars (PLoS genetics, 2017)
Many plant cells can be reprogrammed into a pluripotent state that allows ectopic organ development. Inducing totipotent states to stimulate somatic embryo (SE) development is, however, challenging due to insufficient understanding of molecular barriers that prevent somatic cell dedifferentiation. Here we show that Polycomb repressive complex 2 (PRC2)-activity imposes a barrier to hormone-mediated transcriptional reprogramming towards somatic embryogenesis in vegetative tissue of Arabidopsis thaliana. We identify factors that enable SE development in PRC2-depleted shoot and root tissue and demonstrate that the establishment of embryogenic potential is marked by ectopic co-activation of crucial developmental regulators that specify shoot, root and embryo identity. Using inducible activation of PRC2 in PRC2-depleted cells, we demonstrate that transient reduction of PRC2 activity is sufficient for SE formation. We suggest that modulation of PRC2 activity in plant vegetative tissue combined with targeted activation of developmental pathways will open possibilities for novel approaches to cell reprogramming.
Keywords: regulace genové exprese u rostlin; proteiny huseníčku; Plant Shoots; výhonky rostlin; kořeny rostlin; Plant Roots; Repressor Proteins; somatická embryogeneze rostlin; represorové proteiny; Plant Somatic Embryogenesis Techniques; Arabidopsis Proteins; kyseliny indoloctové; Indoleacetic Acids; Gene Expression Regulation, Plant; Arabidopsis